THE WAYS OF MODERNIZATION OF REAL SECTOR OF THE RUSSIAN ECONOMY - V. Afanasyev (Вестник университета)
The perspective of financial and economic crisis is analyzed. Statistical data showed lack of growth of investment investments in development of the production capital. Relevance of modernization of the Russian engineering and administrative education for modernization of the Russian economy is revealed. It is offered to restore in system of the higher education training of engineers-economists (engineers managers) with a branch.